2021
DOI: 10.1039/d1cp01573g
|View full text |Cite
|
Sign up to set email alerts
|

A coarse-grained xDLVO model for colloidal protein–protein interactions

Abstract: Colloidal protein-protein interactions (PPIs) of attractive and repulsive nature modulate the solubility of proteins, their aggregation, precipitation and crystallization. Such interactions are very important for many biotechnological processes, but are...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 100 publications
(160 reference statements)
2
21
0
Order By: Relevance
“…Pusara et al . 210 recently developed a coarse-grained xDLVO model to correct for the spherical approximation on the DLVO theory, though the results only show a modest improvement for predicting values as a function of ionic strength on both globular proteins and immunoglobulins. These results are not surprising, as Grünberger et al .…”
Section: Protein-protein and Protein-excipient Interactionsmentioning
confidence: 99%
“…Pusara et al . 210 recently developed a coarse-grained xDLVO model to correct for the spherical approximation on the DLVO theory, though the results only show a modest improvement for predicting values as a function of ionic strength on both globular proteins and immunoglobulins. These results are not surprising, as Grünberger et al .…”
Section: Protein-protein and Protein-excipient Interactionsmentioning
confidence: 99%
“…Notably, it is possible to formulate a more generalized version of eqn (1), which is introduced within our manuscript. 26 From a theoretical point of view, the free energy of the saltdependent binding of BLG can be investigated using molecular dynamics (MD) simulations, 27 but sampling of protein-protein configurations in the total PMF, in eqn (1), beyond the BLG dimer from the crystal structure, was not yet reported. According to the DLVO (Derjaguin, Landau, Verwey, and Overbeek) theory, 28 the PMF consists of the electric double-layer forces and vdW interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the calculation of the PPIs beyond the spherical-shaped particles, as commonly used in DLVO, was introduced within a xDLVOcoarse-grained (CG) model. 26 Beyond the DLVO theory and the extended models, W 22 (a) can be estimated using MD and Monte Carlo simulations with both all-atom 32,33 and CG 34 protein representations. The results of these computationally intensive methods have shown that even if the detailed structural and charge characteristics of the protein is properly preserved, other macroscopic features significantly affect the total PMF.…”
Section: Introductionmentioning
confidence: 99%
“…This theory has also been used to study bovine serum interaction to different solid surfaces 33 . This theory has also been modified to study protein–protein interaction 34,35 …”
Section: Introductionmentioning
confidence: 99%
“…33 This theory has also been modified to study protein-protein interaction. 34,35 All these studies suggest that the surface energetics approach, utilizing XDLVO theory, has the potential to understand protein interaction to ion exchange chromatographic supports, which has never been attempted earlier. Hence, this study is an attempt to find out the interaction behavior of proteins to ion exchange chromatographic material by XDLVO theory/surface energetics approach.…”
Section: Introductionmentioning
confidence: 99%